The Effect of Stock Market Listing on Real Earnings Management: Evidence From Algerian Companies - Bilal Kimouche (Naše gospodarstvo/Our economy, 2021)
This paper aims to explore the effect of the Algiers Stock Exchange listing on real earnings management. The study included 14 non-financial non-listed companies during the period 2015-2019 and six non-financial listed companies during the period 2010-2019. Due to the small number of companies listed on the Algiers Stock Exchange, the period of study was extended in the case of listed companies to provide enough observations. The measurement of real earnings management is based on the model of abnormal cash flows from operations (Roychowdhury, 2006), while the hypothesis testing is based on a model of multiple linear regression. The results indicate that the company size and the nature of financial statement (consolidation) do not have any effect on real earnings management in Algerian companies. The results are not consistent with the author’s hypothesis about the positive effect of stock market listing on real earnings management. The empirical evidence suggests that the Algiers Stock Exchange listing has had a negative effect on real earnings management in Algerian companies. This might be due to the scrutiny of auditors and regulators as the number of companies is easy to control, which decreases the opportunity for Algerian companies to rely on real earnings management in accordance with the opportunistic or informational view.